An instant responsive polymer driven by anisotropy of crystal phases. Issue 1 (29th November 2017) - Deng, Heng; Dong, Yuan; Zhang, Cheng; Xie, Yunchao; Zhang, Chi; Lin, Jian
Abstract : An unprecedented responsive mechanism in a single-layered PVDF film is reported, in which a responsive shape change is driven by the anisotropy of crystal phases. Abstract : We report a new type of responsive polymer film which is composed of pure poly(vinylidene fluoride) (PVDF) and is prepared using a simple solution-casting method. This responsive PVDF film possesses an anisotropic spatial distribution of the α phase and β phase, resulting in a fast response rate, high sensitivity, and robust responsiveness to organic vapors. Experimental and computational studies illustrate that α-phase PVDF exhibits a much stronger swelling ability in acetone vapor than β-phase PVDF. Anisotropic swelling induces internal stresses, offering a driving force for macroscopic shape transformation. This newly unveiled mechanism endows the material with new functionalities for fabricating devices such as a magnetically controlled soft tumbler and a chemi-mechanical sensor. Furthermore, crystal phase anisotropy in the PVDF film can be easily programmed into origami patterns by direct laser writing (DLW) for driving reversible three-dimensional (3D) shape transformation of the film.